Application of Green Accounting: Potential Profit from Waste Utilization of Chicken House Business - Akhmad Akram Hirman; Syamsinar Syamsinar; Anna Sutrisna Sukirman; Loso Judijanto; Encep Sopandi (Universitas KH. Abdul Chalim Mojokerto, 2024)
Environmental accounting, namely green accounting, is accounting for the cost of the environment and it is reported in financial statements. Its cost is recognized as the obligation of the company to the environment. This study aims to: a) calculate the company's profit by deducting revenue with cost including environmental costs, and b) estimate the amount of potential profit resulting from waste processing to produce products with economic value. The research was a case study by collecting data from a chicken house company (RPA) that Hajjah Ani in Makassar owned. Data collection such as estimated sales value and waste processing costs were collected through interviews and observations in this company and then compared with those estimated sales and environmental costs from several slaughterhouse companies around Makassar. Researchers calculated the estimated profit of three alternative processed products: fertilizer, food products, and animal feed. The results showed that each alternative product has different potential in increasing profits from the lowest level of 2% to the highest level of 25% which is compared to the previous profit.